Erdheim-Chester disease with multisystemic involvement: a diagnostic challenge - Nishal, Arpita; Patel, Komal; Bhagat, Vasudha; Patel, Siddhi; Gandhi, Nency; Patwari, Sneha (International Journal of Research in Medical Sciences, 2019)
Erdheim–Chester disease (ECD) is a rare, non-inherited, non- Langerhans form of histiocytosis of unknown origin, first described in 1930. This entity is defined by a mononuclear infiltrate consisting of lipid laden, foamy histiocytes that stain positively for CD68. Individuals affected by this disease are typically adults between their 4th and 6th decades of life. The multi systemic form of ECD is associated with significant morbidity, which may arise due to histiocytic infiltration of critical organ systems. Among the more common sites of involvement are the skeleton, central nervous system, cardiovascular system, lungs, kidneys (retroperitoneum) and skin. The most common presenting symptom of ECD is bone pain. Bilateral symmetric increased tracer uptake on 99mTc bone scintigraphy affecting the periarticular regions of the long bones is highly suggestive of ECD. However, definite diagnosis of ECD is established only once CD68(+), CD1a(−) histiocytes are identified within a biopsy specimen with aid of clinical and radiological data. Here we present a rare case of Erdheim-Chester disease in a 46 year male patient based on clinical data, radiological data, histopathological and immunohistochemistry findings.